Electrochemical preparation of nano silver by combining high DC voltage with anodic plasma - Hung, Nguyen Duc; Nam, Vu Nang; Trung, Le Van; Dung, Tran Thi Ngoc (Vietnam Journal of Science and Technology, 2019)
Silver nanoparticles (AgPNs) were prepared by high-voltage electrochemical methods using silver anode to produce silver ions and hydrogen gas at the cathode from electrolysis of distilled water as solvents. The electrolyte solution resulting from the AgPNs product obtained does not contain ions of the electrolyte solution such as conventional chemical or electrochemical methods. Silver anode dissolution process will provide Ag+ and disperse it into distilled water. The process of generating H2 from the electrolysis of H2O disperses into distilled water and escapes upward towards the anode due to the arrangement of the electrolytic vaporizer vertically above the anode and the cathode below. Ag+ and H2’s encounter in the aqueous solution will take the oxidation-reduction reaction to form AgPNs. Due to the high-voltage DC electrolytic processes that generate gas on the electrodes, both high-voltage and high magnetic fields, as well as high water-distillation resistance, will increase the solution temperature as favorable conditions to form an electrochemical plasma on the electrodes. The plasma electrode process that separates water into H2 and O2 can occur simultaneously by electrochemical reactions that contribute to the supply of large amounts of gas to participate in oxidative reactions - reducing the formation of AgPNs. The properties of the AgPNs solution prepared by high-voltage DC lines were determined by UV-Vis, electrical conductivity, TEM, zeta potential, particle size distribution as well as content determined by weight lost method, Faraday’s law and AAS analysis. Anodic plasma can be generated by stable high voltage mode to decompose water that supports electrochemical reactions that form AgPNs with structural, physicochemical and structural properties as well as comparable constituents be with the current methods.